Evaluating the Efficacy of Chitosan Extracted from Crab Shells for the Preservation and Shelf-life Extension of Strawberries - S. K., Anusha Shree; Krishnamoorthy, Vishwakarma Ravindrakumar; S., Jagadeeswari; B., Kirthiga (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A natural biopolymer derived from crab shells, was extracted and characterized by Fourier transform infrared spectroscopy (FTIR). The physicochemical properties and antimicrobial activity of chitosan (CH) in combination with cellulose derivatives like Carboxy Methyl Cellulose (CMC) and hydroxypropyl methylcellulose (HPMC) against various test organisms were evaluated in this study. The results showed that the combined treatment with CMC and HPMC significantly inhibited fungal decay and enhanced fruit quality attributes such as firmness, colour, and nutritional content. Moreover, the combination of HPMC and CH exhibited the highest zone of inhibition for Pseudomonas and Rhizopus at concentrations 2 & 3%. The combined treatment of CH and CMC with HPMC exhibited significant antibacterial activity against all tested organisms. In addition, the titratable acidity levels in strawberry fruits significantly decreased during cold storage, with uncoated fruits exhibiting lower values compared to those coated with chitosan. In conclusion, the efficacy of the chitosan was confirmed in enhancing the postharvest preservation of strawberries, particularly in mitigating ripening processes, minimizing microbial growth, and enhancing fruit firmness. The findings from this study could pave the way for the development of eco-friendly preservation strategies, promoting food security and extending the marketability of strawberries.